Analisis Sentimen Masyarakat Berdasarkan Komentar Kerja Sama Tiktok Shop dan Tokopedia di Instagram Menggunakan Metode Naïve Bayes Classifier - Zaenab Kurnia; Amalina Maryam Zakiyyah; Nur Qodariyah Fitriyah; Agus Milu Susetyo (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The reopening of the Tiktok Shop and collaboration with Tokopedia has caught the public's attention. That's proven by a post on Instagram about their collaboration that received various responses. This research aims to conduct sentiment analysis to ascertain whether the public approves of the two's partnership. The Naïve Bayes Classifier method was used to analyze 641 comment data from the period 11 December 2023 to 11 February 2024. The results show the composition of positive, negative, neutral sentiment and unclassified data, as well as accuracy, precision and recall. Of the 641 data recorded, there were 269 neutral sentiment data, 194 negative sentiment data, 176 positive sentiment data, and 437 unclassified data. The Naïve Bayes Classifier model with oversampling techniques obtained an accuracy of 83%, precision of 81%, and recall of 93%.